The Stryker Brigade Combat Team - Vick, Alan J.; Orletsky, David T.; Pirnie, Bruce R.; Jones, Seth G. (RAND Corporation, 2023)
Examines alternative means to decrease the deployment time for the new Army medium-weight brigade, comparing air and sealift from the United States with air and fast (but short-range) sealift from forward bases or preposition sites. Historical experience and an assessment of U.S. regional interests are used to determine how much warning time the United States typically has before major force deployments and where it is most likely to deploy such forces